2005
DOI: 10.1158/1055-9965.epi-04-0681
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Peroxisome Proliferator–Activated Receptor γ and Diet in Etiology of Colorectal Cancer

Abstract: The peroxisome proliferator -activated receptor ; (PPAR;) is one of a group of ligand-activated nuclear receptors responsible for regulation of glucose, lipid homeostasis, cell differentiation, and apoptosis. The 12 proline-to-alanine (Pro12Ala) substitution polymorphism in PPARg produces proteins with lower activity. Variation in PPARg expression in the bowel and the role of dietary fatty acids as ligands for PPAR; led investigation of whether the associations of diet with colon and rectal cancer risk were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…As shown in Figure 2, rs1229984 of the ADH1B gene was significantly associated with CRC in the Asian and Caucasian populations (the overall OR = 1.18, 95% CI = 1.01-1.36, p = 0.03). The meta-analysis of rs1801282/P12A/34 C > G of PPARG was involved with 14 studies (Smith et al, 2001;Jiang et al, 2005;Landi et al, 2003;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Koh et al, 2006;Kuriki et al, 2006;Theodoropoulos et al, 2006;Vogel et al, 2007 ;Kury et al, 2008;Tsilidis et al, 2009;Crous-Bou et al, 2012) among 9132 CRC cases and 12,974 controls. Using the random-effect model, our result indicated that rs1801282-G contributed to the risk of CRC (the overall OR = 1.50, 95% CI = 1.14-1.97, p = 0.004) in the Asian and Caucasian populations.…”
Section: Quantitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, rs1229984 of the ADH1B gene was significantly associated with CRC in the Asian and Caucasian populations (the overall OR = 1.18, 95% CI = 1.01-1.36, p = 0.03). The meta-analysis of rs1801282/P12A/34 C > G of PPARG was involved with 14 studies (Smith et al, 2001;Jiang et al, 2005;Landi et al, 2003;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Koh et al, 2006;Kuriki et al, 2006;Theodoropoulos et al, 2006;Vogel et al, 2007 ;Kury et al, 2008;Tsilidis et al, 2009;Crous-Bou et al, 2012) among 9132 CRC cases and 12,974 controls. Using the random-effect model, our result indicated that rs1801282-G contributed to the risk of CRC (the overall OR = 1.50, 95% CI = 1.14-1.97, p = 0.004) in the Asian and Caucasian populations.…”
Section: Quantitative Synthesismentioning
confidence: 99%
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a total of 26 studies (6-12,14-21,23-33) involving 11,627 cases and 16,050 controls were ultimately analyzed for P12A, five studies (13-16,33) involving 1,819 cases and 2,642 controls for C161T. Five studies (6,15,17,28,33) sorted the data in different race or different tumor types, therefore, each group in these studies was considered separately for pooling subgroup analyses. Table I presents the main characteristics of these studies.…”
Section: Study Characteristics and Meta-analysis Resultsmentioning
confidence: 99%
“…Among 26 publications, 24 were published in English, and two (8,12) were in Chinese. There were 11 Asians groups (8,(10)(11)(12)(14)(15)(16)19,28,33), 13 Caucasian groups (6,7,9,13,18,21,23,24,27,28,33), and 13 American groups (6,17,20,25,26,28,29,(30)(31)(32). HWE had been tested in most controls, and most of the controls were in HWE, there were five studies (17,19,23,29,32) without genotype distribution in detail.…”
Section: Study Characteristics and Meta-analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation